PEMBINAAN AKHLAKUL KARIMAH REMAJA UNTUK MENGHADAPI TANTANGAN ERA SOCIETY 5.0 DI MAN 1 LAMPUNG TIMUR - Muhammad Ilham; Sulthon Syahril; Eti Hadiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the strategy of character development, particularly akhlakul karimah, for adolescents in addressing the challenges of the Society 5.0 era at MAN 1 Lampung Timur. Society 5.0 is characterized by the integration of digital technologies into every aspect of life, which significantly affects youth behavior and values. This study employs a qualitative descriptive method, using data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that the character-building efforts at the institution are implemented through four main approaches: ta’lim (teaching), habituation, training, and mujahadah (spiritual struggle). Each approach is integrated into daily school life, aiming to instill Islamic values in both offline and online behavior. Despite challenges such as the negative influence of social media and a lack of digital ethics awareness among students, the school has demonstrated a strong commitment to embedding Islamic morality within the educational environment. The results show that this model of character development is relatively effective in forming religious, disciplined, and responsible students, equipping them with the necessary resilience to face the complex dynamics of the digital era.